On the issue of shielding properties of plasma in the outside separatrix region of U-3M - Konovalov, V.G.; Chechkin, V.V.; Ggrigor’eva, L.I.; Shapoval, A.N. (Вопросы атомной науки и техники, 2014)
When providing experiments on RF plasma production and heating in U-3M torsatron there was observed sudden decrease (up to two times) of mean confined plasma density during step-rise of an RF antenna voltage. Trying to analyze the reason of this effect we estimated a screening effect of the out-separatix plasma, characteristics of which were recently measured. It was found that at the plasma confinement border the attenuation is: 6 % for H2, 1.4, 7, 6 % for C, Fe and Ti atoms correspondingly. This is much below the result of attenuation (~70 %) estimated in [1] for the flux of laser ablated C atoms.